Distribution of Work Load at Main Controller Level Using Enhanced Round Robin Scheduling Algorithm in A Public Cloud - Thejesvi, G; Anuradha, T (International Journal of Computer Sciences and Engineering, 2025)
The enormous development in the computer and communication technology led to use various web based software applications using with the Internet. Cloud computing is an emerging technology where millions of clients and individuals use various cloud services like storage, software’s and infrastructure on rental basis. Tremendous increase in the number of users has led to some issues and problems. One of the main issues is balancing the work load and increasing the performance of the system. An efficient and dynamic algorithm called “Enhanced Round Robin scheduling algorithm” has been proposed in this paper for balancing the load. The work distribution to the various balancers by the main controller is done using two parameters: one is balancer status (idle, normal and overload) and the other is percentage of overall balancer status (idleness and normalness). Based upon these parameters, the balancers are sorted and stored in a list. The work is distributed to various balancers in a round robin fashion.